Alkaline Phosphatase Activity and Endotoxemia After Infant Cardiothoracic Surgery. Issue 3 (March 2019) - Davidson, Jesse A.; Urban, Tracy T.; Tong, Suhong; Maddux, Aline; Hill, Gerald; Frank, Benjamin S.; Watson, John D.; Jaggers, James; Simões, Eric A. F.; Wischmeyer, Paul
ABSTRACT: Objective: Infant cardiopulmonary bypass (CPB) increases intestinal permeability leading to endotoxemia. Alkaline phosphatase (AP) reduces endotoxin toxicity in vitro but its effects on endotoxemia in human disease are poorly understood. We assessed the association between serum AP activity and endotoxemia in infants undergoing CPB and determined the effect of ex vivo addition of AP on endotoxemia. Methods: Prospective cohort study of 62 infants ⩽120 days of age undergoing CPB. AP activity and Endotoxin Activity Assay (EAA) were measured pre-operatively, during rewarming, and 24 h after cardiac intensive care unit admission. In 22 subjects, EAA was measured in pre-operative and rewarming whole blood samples with/without addition of 1, 600 U/L of human liver AP. Results: AP activity decreased during CPB (mean decrease 94.8U/L; P < 0.0001). Median EAA was 0.41 pre-operation, rose to 0.52 ( P < 0.05) during rewarming, and remained stably elevated at 24 h. Subjects with low pre-operative AP activity had significantly higher pre-operative (0.47 vs. 0.36; P < 0.05) and rewarming (0.59 vs. 0.43; P < 0.01) EAA with a trend toward higher EAA at 24 h (0.52 vs. 0.45; P = 0.12). Subjects with low rewarming AP activity showed similar differences that did not reach statistical significance. Ex vivo addition of human liver AP decreased pre-operative EAA by 29% ( P < 0.001) and rewarming EAA by 51% ( P < 0.0001). Conclusion: Endotoxemia is common in infants undergoing CPB. Native AP activity and endotoxemia are inversely related and ex vivo addition of exogenous AP reduces whole blood EAA. Future research should evaluate AP as a therapy to reduce the harmful effects of endotoxemia following infant CPB.